The Effect Of Rheumatic Exercises On The Ability Of The Elderly In Carrying Out Daily Activities In Kampung Baru Village - Lily Putri Marito (International Journal of Public Health, 2025)
Health problems in the elderly are increasingly becoming a major concern at global and national levels, along with increasing life expectancy. One of the most common health problems faced by the elderly is musculoskeletal disease, including rheumatism. This study aimed to determine the effect of rheumatic exercise on the ability of elderly individuals to perform daily activities. This study is a quantitative study using a quasi-experimental one-group pre-test and post-test design. The results showed that The results of the Wilcoxon rank test were p = 0.000, which was smaller than α = 0.05. This study shows the effect of rheumatic exercise on the ability of the elderly to perform daily activities. This shows that rheumatic exercise is an effective intervention to support the ability of the elderly to face physical and psychological challenges due to aging and chronic diseases, such as rheumatoid arthritis.